Does Participatory Budgeting Improve Decentralized Public Service Delivery? - Diether W. Beuermann; Maria Amelina (Inter-American Development Bank (IDB), 2014)
This paper provides the first experimental evaluation of the participatory budgeting model showing that it increased public participation in the process of public decision making, increased local tax revenues collection, channeled larger fractions of public budgets to services stated as top priorities by citizens, and increased satisfaction levels with public services. These effects, however, were found only when the model was implemented in already-mature administratively and politically decentralized local governments. The findings highlight the importance of initial conditions with respect to the decentralization context for the success of participatory governance.
hdl:11319/6699
Keywords: H11; H41; H43; H70; P35; 330; decentralization; participatory budgeting; training; technical assistance; Russia